Pengembangan Sistem Manajemen Pemeliharaan Preventif Mesin berbasis Web (Studi Kasus: PT Valeo AC Indonesia) - M Reza Syahputra A; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
This research discusses the development of a web-based machine preventive maintenance management system and takes a case study in PT Valeo AC Indonesia, which is a manufacturer of wiper blades for cars. In the industrial world, the importance of the level of machine performance requires companies to implement a machine maintenance policy. The policy adopted by PT Valeo AC Indonesia is preventive maintenance. Unfortunately, there are some problems found starting from the implementation of policies that are still carried out using a paper system, the schedule is not fixed, there is no warning system, and the problem of spare parts supply. These problems can be solved by building a web-based preventive machine maintenance management system. The system has various functions such as task management, schedule management, asset management, and user management. Its implementation utilizes the Laravel framework. After completion, the system is tested and the result is 100% valid and can run on all web browsers without any problems.